Service Quality Improvement at CV. Citra Tiara (Citi Trans) Bandung (The Indonesian Journal of Business Administration, 2012)
CV. Citra Tiara was established in 2005, as a shuttle service provider. Through â€œCiti Transâ€ brand, this company is a pioneer of executive shuttle service that introduces personal seat system. Within last two years, Citi Trans has never achieved occupancy target that defined by the management. That was an impact of the intense competition in shuttle service industry. It also because Citi Trans was unable to achieved customer expectation through its services.Root cause need to be determined to know why Citi Trans unable to achieve the occupancy target. Internal analysis, business situation analysis, and service quality analysis need to be conducted. Internal analyses were conducted by analyze the corporate strategy, business strategy, Segmenting Targeting and Positioning (STP), and marketing mix (7P) of Citi Trans. Business situation analyses were conducted by analyze Porterâ€™s Six Forces and 5C of Citi Trans business environment. Service quality analysis was conducted by Importance-Performance Analysis (IPA) method by measuring five dimensions of service quality (SERVQUAL). Based on above analyses, the root causes are lack number of Citi Trans pool, that cause lack of variation of route/destination that offered by Citi Trans and also customersâ€™ expectation on Citi Trans service quality were not fulfilled.Objective of this research is to give service quality improvement recommendation to Citi Trans with program and implementation plan to increase customer satisfaction. These recommendations are expected to help Citi Trans to achieve the occupancy target. Â Keywords: Citi Trans Bandung Shuttle Service, Service Quality (SERVQUAL), Importance-Performance Analysis (IPA)